The effect of sociodemographic factors on the risk of poor mental health in Akron (Ohio): A Bayesian hierarchical spatial analysis. (August 2021) - Yankey, Ortis; Amegbor, Prince M.; Lee, Jay
Highlights: We examine the association of sociodemographic factors on mental health risk in the city of Akron (Ohio). We used Spatial Bayesian models which accounted for spatial and sociodemographic effect on the risk of mental health. Poor mental health risk was positively associated with the proportion of people lacking sufficient sleep, people below poverty, and the percentage of married couples. Area specific effect showed differential spatial patterns of effect across the city. Area specific effect is necessary for targeted policy interventions to mitigate mental health risk. Abstract: We examined the association of sociodemographic factors on mental health risk within the city of Akron (Ohio). A Spatial Bayesian Hierarchical model was used in this study. We found that the risk of poor mental health was positively associated with the proportion of people lacking sufficient sleep (RR = 0.42, 95% CI:0.22-0.62), the percentage of people below poverty (RR = 0.12, 95% CI: 0.09, 0.16), and the percentage of married couples (RR = 0.02, 95% CI: -0.05, 0.08). On the contrary, the percentage of female population (RR = -0.06, 95% CI: -0.13, 0.01), the percentage of the black population (RR = -0.05, 95% CI: -0.08, -0.02), and the college-educated population (RR = -0.03, 95% CI: -0.09, 0.04) was negatively associated with the risk of poor mental health. We also found that the sociodemographic variables have spatially varying effects across different neighborhoods. Future studies will examine the joint spatial effect of poor mental health risk and suicide ideation in the study area.